1987
DOI: 10.3109/01902148709069601
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in Coupled Beta-Adrenergic Receptor and Adenylate Cyclase System during Bleomycin-Induced Lung Fibrosis in Hamsters

Abstract: The purpose of this study was to evaluate the coupled beta-adrenergic receptor (BAR) and adenylate cyclase (AC) system of the lung during the course of the bleomycin-(Bleo) induced pulmonary fibrosis in hamsters. The BAR population, dissociation constants (Kd), AC activity, and its sensitivity to various stimulators were studied at 2, 4, 7, 14, and 21 days after intratracheal administration of either 1 unit of Bleo or an equivalent volume of saline. The BAR population in the lungs of Bleo-treated animals did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
6
2
Order By: Relevance
“…Although these observations differ from our current results (in that we do not observe differences in cAMP generation (Fig. 3), Giri et al (1987) reached a similar conclusion regarding impairment in the cAMP pathway as partly responsible for the fibrogenic response. Therefore, fibrogenesis in human lung may share some commonality with experimentally induced pulmonary fibrosis in rodents.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…Although these observations differ from our current results (in that we do not observe differences in cAMP generation (Fig. 3), Giri et al (1987) reached a similar conclusion regarding impairment in the cAMP pathway as partly responsible for the fibrogenic response. Therefore, fibrogenesis in human lung may share some commonality with experimentally induced pulmonary fibrosis in rodents.…”
contrasting
confidence: 57%
“…Other, nontraditional signaling pathways activated by EP receptors perhaps contribute to the disparate response to PGE 2 compared with other agents that we tested. Giri et al (1987) described that signaling via the ␤-adrenergic receptor/adenylyl cyclase system is defective in a rat model of bleomycin-induced pulmonary fibrosis (Giri et al, 1987). Although these observations differ from our current results (in that we do not observe differences in cAMP generation (Fig.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…With this observation in mind, we checked the expression of β 2 -adrenoceptors in other data sets. Our in-house next-generation sequencing (NGS) data of murine bleomycin models, the mouse AAV6.2m-TGF-β1 overexpression model and TGF-β-treated primary HLF and the analysis of external NGS studies (GSE1066; Konishi et al, 2009;GSE52463;Nance et al, 2014) together with current and earlier literature (Giri et al, 1987;Bauer et al, 2015) revealed a general down-regulation of β 2 -adrenoceptors in IPF lung samples and IPF-related in vitro and in vivo models. This is in contrast to our observation that, in vitro, cultures of IPF-LF and HLF showed no significant differences in expression of β 2 -adrenoceptors.…”
Section: Discussionmentioning
confidence: 84%
“…In our opinion, anti-fibrotic effect of the drug in bleomycininduced fibrosis can be partially is connected with disturbance of serotonin mechanism fibroblast proliferation and collagen synthesis by fibroblasts both and levels of TGF-β 1 , connective tissue growth factor and plasminogen activator inhibitor-1 is decreased in the lung [44]. Some authors attribute the synthesis of collagen fibers in the lung to adrenergic receptors activity [45,46]. Due to the fact that spiperone is α1B-adrenoceptor antagonist, we do not exclude the realization of adrenergic mechanism.…”
Section: Cd34mentioning
confidence: 97%